Data Acquisition System for Resistance Measurement of High-temperature Superconductors - Yahya, Ahmad Kamal; Abd Shukor, Roslan; Md Salleh, Faizah (Universiti Putra Malaysia Press, 1996)
This paper discusses the design of a data acquisition system based on the 80486 microcomputer serving as a controller connected via a PC-Lab 848B card to digital multimeters and a temperature controller using IEEE 488 standard bus. The system is able to log, store and plot temperature versus resistance readings. Resistance measurement on YBa2Cu3074l) phase is reported and compared with previous results. Measurements on (YO.5 EUO.5)Ba2CuS07.S showed an increase in Tc onset and Tc zero; this was explained in terms of change in the internal pressure in the CuO planes due to partial substitution of larger Eu3+ in place of y3+. This data acquisition system is simple to use and very sensitive in detecting small variations in transition temperatures. The temperature can be measured with a precision of 0.1 K and accuracy of ± I K, which is the limit of the platinum resistor temperature sensor. The absolute-zero offset value is less than 0.1 K.